Oligopoly and Collusion in the Colombian Electricity Market - Marin, Jorge Barrientos; Marin, Hector Gomez (International Journal of Energy Economics and Policy, 2022)
The Wholesale Electricity Market –WEM– in Colombia was created with Laws 142 and 143 of 1994 with the aim of promoting and preserving competition among agents and guaranteeing an efficient energy spot price. However, in practice the market works as an oligopoly in competition; evidence indicates there is market concentration, without reaching abuse of dominant position or price collusion, at least not explicitly. This paper develops a game model with incomplete information, in which there is at least a Perfect Bayesian Equilibrium with implicit collusion among agents. That is, it is highly likely that, under certain conditions, some generators tacitly follow the price strategies of agents with greater installed generation capacity (pivotal) and hence propose similar bid prices. The empirical analysis shows that scenarios of radical and similar increases in bid prices, for different generators, are a pattern present in the WEM.